Peningkatan Hasil Belajar dan Bernalar Kritis Kelas X SMAN 1 Pagak Materi Bersikap Kritis dan Bertanggung Jawab terhadap Media Massa melalui Problem Based Learning - Yoanna Francisca Dwi Purnastiti (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
The teaching methods applied in grade X at SMAN 1 Pagak are still lacking in variety, leading to students' low critical reasoning skills and the failure to achieve the target in the proficient and skilled categories. This research aims to improve students' learning outcomes and target achievement through the implementation of Problem Based Learning (PBL). The Classroom Action Research (CAR) was conducted in two cycles with the material